The Importance of Critical Thinking in the Process of Personal Development (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
In modern socio-economic conditions, one of the priority areas of higher education is the training of highly qualified specialists who have the necessary professional knowledge, are able to make independent and responsible decisions, and are creative in non-standard conditions. For example, the professional activity of a future lawyer includes knowledge of laws, regulatory legal documents, the ability to interpret them and apply them in practice. The competence of a lawyer is based on the ability to freely adapt to various situations, the ability to creatively solve problems, and openness to innovation and independent learning. These qualities are extremely relevant for a legal profession that requires high intellectual potential, on the basis of which the skills of comprehensively understanding existing problems and creatively solving them are formed. A high level of critical thinking is of great importance for this professional competence.